2022
DOI: 10.1177/15347354221086663
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Prophylactic Traditional Chinese Medicine on Skin Toxicity of Afatinib in EGFR Mutation-Positive Advanced Lung Adenocarcinoma: A Single-Center, Prospective, Double-Blinded, Randomized-Controlled Pilot Trial

Abstract: Objectives: To evaluate the efficacy of prophylactic traditional Chinese medicine (TCM) on skin toxicities in patients with advanced lung adenocarcinoma treated with first-line epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) in a randomized-controlled trial (RCT). Materials and methods: This pilot study was a prospective, single-center, double-blinded RCT. The study enrolled patients with a new diagnosis of locally advanced and metastatic lung adenocarcinoma harboring EGFR mutations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Immune checkpoint therapies using anti-programmed death 1 (PD-1) and anti-programmed death ligand-1 (PD-L1) have transformed the management of lung adenocarcinoma and other metastatic malignancies (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune checkpoint therapies using anti-programmed death 1 (PD-1) and anti-programmed death ligand-1 (PD-L1) have transformed the management of lung adenocarcinoma and other metastatic malignancies (24).…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint therapies using anti-programmed death 1 (PD-1) and anti-programmed death ligand-1 (PD-L1) have transformed the management of lung adenocarcinoma and other metastatic malignancies ( 24 ). Even though immune checkpoint inhibitors can greatly improve the prognosis for lung adenocarcinoma patients, a substantial proportion of patients are resistant to them or they prove ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that the combined therapy had a certain effect to prolong mPFS (12.3 vs 8.9 months, P < 0.05) and mOS (28.2 vs 24.2 months, P < 0.05), especially for the patients with exon 21 deletion mutation (L858R) ( Wang et al, 2021 ). At the same time, TCM could delay EGFR-tyrosine kinase inhibitors (EGFR-TKIs) related skin toxicity of any grade and reduce the incidence of grade 3 skin toxicity ( Li et al, 2022 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…In recent years, the value of Traditional Chinese medicine (TCM) in tumor treatment has been high-profile based on its low toxicity and multi-target activity ( Xiang et al, 2019 ). Several randomized controlled trials (RCT) have been conducted to provide clinical evidence for TCM treatment of patients with different types of tumors, including CRC ( Wang et al, 2021b ), breast cancer ( Zhang et al, 2022 ), lung adenocarcinoma ( Li et al, 2022 ), and so on. Erchen Decoction (ECD), a traditional Chinese botanical formula, has been proven to play a significant role in regulating lipid metabolism and used to be applied for treating lipid-disorder-related diseases, such as obesity, hyperlipemia, and so on ( Zhang et al, 2020a ; Luo et al, 2020 ; Ding et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%